ANALISIS PENERAPAN SWOT TERHADAP PENINGKATAN PENJUALAN PADA PT.NUSASEMBADA BANGUNINDO DI MAKASSAR - A. Husnawaty AR (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
This study aims to look at the application of the SWOT analysis (Excellence, Kelelmahan, Opportunities and Threats) of the factors - factors that affect the sales and to analyze the application of SWOT analysis. (Excellence, Weaknesses, Opportunities and Threats) to increase the volume of home sales, especially in PT. Nusasembada Bangunindo in Makassar with the method used is the Swot analysis is an analysis to determine the strengths and weaknesses and the opportunities and threats faced by PT. Nusasembada Bangunindo in Makassar. Results Discussion swot analysis results, demonstrating excellence in marketing-type housing 36 which is achieved by the company average-average of 13.76 %. While the weakness of the company is due to selling prices applied by the company is higher when compared with competitors as well as the promotion has not been adequately perform the type of home sales volume declined. Based on the results of swot analysis in marketing homes Swot type 36 , the formulation used by the company is through the marketing mix (product, price promotion and distribution channels)